2014
DOI: 10.1155/2014/157523
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Pederson Scale in Surgical Extraction of Impacted Lower Third Molars: Proposal of New Scale

Abstract: The aim of this study was to evaluate the clinical reliability of the Pederson index in preoperative assessment of the difficulty of surgical removal of impacted mandibular third molars. Pederson index was found to be unreliable predictor of true difficulty with low sensitivity and specificity. A new index (Kharma scale), which takes into consideration the anatomical form of tooth roots, is proposed and evaluated both pre- and postoperatively. The results of the evaluation indicate that the new estimating inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The evaluation of the difficulty of surgical removal of an impacted third molar in the mandible was performed using the Pederson index [ 22 , 23 ]. Based on the impaction according to Winter, the spatial position of the impacted teeth was defined as mesial-angular alignment, horizontal/reversed alignment, vertical alignment, and distal-angular alignment.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of the difficulty of surgical removal of an impacted third molar in the mandible was performed using the Pederson index [ 22 , 23 ]. Based on the impaction according to Winter, the spatial position of the impacted teeth was defined as mesial-angular alignment, horizontal/reversed alignment, vertical alignment, and distal-angular alignment.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the MPS was considered as a reference standard index of surgical difficulty as it found reliable and consistent with operative difficulty by researchers ( 1 , 7 , 8 , 12 ). The results of this study was in agreement with previous studies where the MPS was found significantly correlated with surgical time ( P =0.007).…”
Section: Discussionmentioning
confidence: 66%
“…Kharma scale proposed a new difficulty prediction index based on 4 factors: tooth angulation, the depth of the third molar in the mandible, the relationship with the ramus/space available, and root form ( 7 ). It is similar to Pederson index in that it measures the same parameters in addition to root forms, and close to Yuasa scale ( 3 ) as the former assess the same parameters in addition to tooth angulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third molar surgery is one of the treatments most performed by dentists in daily practice (5,6,11,21). Therefore, various authors agree that this type of surgery should be carried out by qualified professionals, should be evaluated prior upon execution, in order to experience minimal pre-, intra-, and post-operative complications (11,14,18,26,27). This has generated the need to evaluate scales that allow predicting the difficulty that a third molar extraction may have due to the proximity to important anatomical structures (9,10).…”
Section: Discussionmentioning
confidence: 99%